Heat Transfer, Volume 1 2002
DOI: 10.1115/imece2002-32897
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Flow Patterns and Heat Transfer in Confined Jet Impingement

Abstract: The flow field of a 2-D laminar confined impinging slot jet is investigated. Numerical results indicate that there exist two different solutions in some range of geometric and flow parameters. The two steady flow patterns are obtained under identical boundary conditions but only with different initial flow fields. Three different exit boundary conditions are investigated to eliminate artificial effects. The different flow patterns are observed to significantly affect the heat transfer. A flow visualization exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
3
14
0
1
Order By: Relevance
“…A lot of work is documented on flow behaviour and heat transfer of jets. Li et al [1] showed that there exist two different solutions for the flow field in some range of geometric and flow parameters. The use of multiple jets results in a wider range in heat transfer rates and distributions.…”
Section: Introductionmentioning
confidence: 98%
“…A lot of work is documented on flow behaviour and heat transfer of jets. Li et al [1] showed that there exist two different solutions for the flow field in some range of geometric and flow parameters. The use of multiple jets results in a wider range in heat transfer rates and distributions.…”
Section: Introductionmentioning
confidence: 98%
“…They highlighted the importance of Brinkman equation in convection of porous media. Although the literatures show that the jet impingement through non-porous fluid has been studied extensively (see, for example, [15][16][17][18][19][20]), it is noticeable that the jet impingement cooling through porous medium has received relatively less attention. The earlier studies in jet impingement are performed by Martin [15] and Jambunathan et al [16] using direct air impingement onto a solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…They consider the cooling of the heated horizontal surface by parallel flow with the heat source also. Although the literature shows that the jet impingement through pure (non-porous) fluid has been studied extensively (see, for example [15][16][17]), but it is noticeable that the jet impingement cooling through porous medium has received relatively less attention. Prakash et al [18] and Fu and Huang [19] have considered the impinging jet studies in enclosures with and without a porous layer.…”
Section: Introductionmentioning
confidence: 99%